Simple and Rapid Method for Detecting Biofilm Forming Bacteria - Kalia, Vipin Chandra (Indian J Microbiol, 2016)
Biofilm forming bacteria play a vital role in causing infectious diseases and for enhancing the efficiency of the bioremediation process through immobilization. Different media and conditions have been reported for detecting biofilm forming bacteria, however, they are not quite rapid. Here, we propose the use of a simple medium which can be used for detecting biofilm former, and also provide a mechanism to regulate the expression of biofilm formation process. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s12088-016-0616-2) contains supplementary material, which is available to authorized users.